Semiotik der Verewigung Versuch einer Typologie anhand literarischer Texte um 1800 - Gut, Markus (Brill, 2020)
This monograph systematically examines, within the intersection of literary and cultural studies as well as semiotics, intralinguistic procedures intended to record information as permanently as possible. In doing so, it succeeds for the first time in presenting a typology that describes semiotic procedures in the pursuit of 'eternalization' that go far beyond the period of around the year 1800. This monograph includes an extended English general overview and summary.